2023
DOI: 10.1186/s12711-023-00791-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental variance-based resilience selection on the gut metabolome of rabbits

Abstract: Background Gut metabolites are key actors in host-microbiota crosstalk with effect on health. The study of the gut metabolome is an emerging topic in livestock, which can help understand its effect on key traits such as animal resilience and welfare. Animal resilience has now become a major trait of interest because of the high demand for more sustainable production. Composition of the gut microbiome can reveal mechanisms that underlie animal resilience because of its influence on host immunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…2 ). The latter supported the differences found in the gut metabolite formiminoglutamate, which was found to be lower in the rabbits from the low VE population [ 40 ]. Differences in glutamate levels were also observed [ 40 ].…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…2 ). The latter supported the differences found in the gut metabolite formiminoglutamate, which was found to be lower in the rabbits from the low VE population [ 40 ]. Differences in glutamate levels were also observed [ 40 ].…”
Section: Resultssupporting
confidence: 65%
“…2 ). A gut metabolomic study suggested differences in the feed efficiency between these rabbit populations [ 40 ] which could explain the differences in the abundance of Ruminococcus bromii . Ruminococcus bromii is a keystone in breaking down starch, allowing other gut microbiota species to cross-feed [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a noteworthy study by Blasco et al in 2017, which focused on divergent selection for variability in rabbit litter size, challenges this notion. Subsequent investigations on this particular population, employing genomic analysis [18] and metabolic pro ling [20], unveiled a link between this variability and a more comprehensive notion of animal resilience. These ndings align with later studies that also observed associations between genomic pro les and resilience, even in the absence of intentional stress induction, as in our current study [16,38].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, recent investigations have prioritized unraveling the association between the microbiome and resilience. Studies have examined resilience in various contexts, encompassing the resistance of coral to climate changes [44,45], the practical implications of microbiome engineering in plants [20], and the role of microbial composition in thermal stress adaptations across different animal species, including tadpoles [46], Drosophila [47], and mice [48]. However, within the domain of livestock, only one study conducted by Casto-Rebollo et al in 2023 in rabbits has explored the relationship between the microbiome and resilience [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation